2017
DOI: 10.1016/j.abb.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

All three human scavenger receptor class B proteins can bind and transport all three macular xanthophyll carotenoids

Abstract: Carotenoids are plant pigment molecules that are potent antioxidants. Carotenoids cannot be synthesized de novo; therefore, their dietary intake and transport to various tissues are essential to harness their health benefits. Two of the three scavenger receptor class B (SRB) proteins, SR-B1 and CD36, have been implicated as carotenoid transporters in lower species and in various tissues of higher animals. The function of the third SRB protein, SR-B2, in carotenoid transport is unknown. Using surface plasmon re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Supplementation of meso-zeaxanthin along with lutein and zeaxanthin has shown improvements in psychophysical testing compared to placebo, but its impact on the progression of AMD is unclear [77]. Carotenoid-binding proteins have been demonstrated to deposit meso-zeaxanthin into the macula, thus supporting the hypothesis that oral supplementation of meso-zeaxanthin will augment MP density [48]. It is now available commercially, and logically, it should be included in one treatment arm of any potential AREDS3 trial, if that study were to be conducted one day.…”
Section: The Future Of Amd and Mpmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation of meso-zeaxanthin along with lutein and zeaxanthin has shown improvements in psychophysical testing compared to placebo, but its impact on the progression of AMD is unclear [77]. Carotenoid-binding proteins have been demonstrated to deposit meso-zeaxanthin into the macula, thus supporting the hypothesis that oral supplementation of meso-zeaxanthin will augment MP density [48]. It is now available commercially, and logically, it should be included in one treatment arm of any potential AREDS3 trial, if that study were to be conducted one day.…”
Section: The Future Of Amd and Mpmentioning
confidence: 99%
“…Recently, Lobo et al reported the presence of ISX (intestine-specific homeobox), a transcription factor that governs carotenoid absorption via SR-B1 and BCO1 mRNA expression, which is regulated by a carotenoid metabolite, retinoic acid [47]. Several studies have revealed that SR-B1 and CD36 can function as carotenoid transporters into the retina [48,49]. The role of the third SR-B family member, SR-B2, in carotenoid transport was not clear until Shyam et al reported that all three human SR-B proteins (SR-B1, SR-B2, and CD36) were capable of binding all three macular carotenoids, and once delivered to the retina, they are stabilized by the presence of high levels of specific binding proteins in the macula [48].…”
Section: Macular Carotenoid Binding Proteins and Mp Transport To Retinamentioning
confidence: 99%
“…These carotenoids have been identified as lutein, zeaxanthin, and meso -zeaxanthin [4–7], of which lutein and zeaxanthin originate from the diet, whereas meso -zeaxanthin comes mainly from an isomerization reaction of lutein in the retinal pigment epithelium (RPE) [8, 9]. The uptake of macular carotenoids has been reported to be a selective and active absorption process involving many transporter proteins and enzymes [1, 1014]. Glutathione S-transferase Pi isoform (GSTP1) and steroidogenic acute regulatory domain protein 3 (StARD3), are the two carotenoid-binding proteins responsible for the specific retinal distribution of zeaxanthin and lutein, respectively [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively low blood level of lutein (0.1–1.44 μmol/L in USA; 0.26–0.70 μmol/L in Europe) and especially of zeaxanthin (0.07–0.17 μmol/L in USA; 0.05–0.13 μmol/L in Europe), human retina accumulates high amounts of carotenoids (lutein, zeaxanthin and meso -zeaxanthin) in the macula, reaching as much as 1 mM [ 12 , 13 , 14 ]. It was established that the mechanism behind the preferential and selective accumulation of these xanthophylls in the macula involves the participation of all three human SR-B proteins (SR-B1, SR-B2 and CD36) [ 15 , 16 ]. Specifically, all three proteins were able to take up significant amounts of zeaxanthin and the uptake was increased in the presence of HDL.…”
Section: Introductionmentioning
confidence: 99%